PEMBUATAN PUPUK ORGANIK CAIR BERBAHAN KEONG MAS PLUS (POCMAS-PLUS) DAN APLIKASINYA PADA TANAMAN ROSELLA PADA FASE SEEDLING - Ketut Sumantra; Ketut Widnyana (Jurnal Abdi Insani, 2022)
The golden snail (Pomaceae canaliculata) is an organism that destroys cultivated plants with a loss rate of 10-40%. The threat of the golden snail can become an opportunity that has economic and ecological value if it is used as liquid organic fertilizer (POCMAS-Plus). The POCMAS-Plus product, as a result of the training, can support sustainable agricultural development in Subak Lepud, Baha Village, and overcome the failure of rosella seedling growth due to less consistent growth. The activity aims to provide skills to subak members in making liquid organic fertilizer made from snails and applying POCMAS-Plus to rosella plants in the nursery phase. The implementation method consists of 1) Socialization activities and training on using golden snails as liquid fertilizer. 2) Demonstration of making liquid organic fertilizer and 3) application (POCMAS-Plus) to Rosella plants in the nursery phase. Paired T-test was carried out to determine the difference in the growth of rosella seedlings between those given and those not given POCMAS-Plus on growth uniformity, root length, seedling length, and the number of leaves. The pre-test results showed that most participants knew what organic fertilizer was. Still, only half knew the ingredients that could be used as liquid organic fertilizer, and most did not know about the process of making liquid organic fertilizer. All participants know and can make fertilizer independently. The POCMAS-Plus application increased the growth and uniformity of rosella seedlings. The results of the POCMAS-Plus application show that golden snails can be used as the main ingredient for making liquid organic fertilizer so that the growth and uniformity of rosella seedlings are better.